UMUMIY O‘RTA TA’LIM MUASSASASI O‘QUVCHILARNING JISMONIY RIVOJLANISHIDA GIMNASTIKA MASHQLARINING ROLI VA SAMARADORLIGI (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article highlights the role of gymnastics exercises in the physical development of students in general secondary education institutions, their significance in the formation of a healthy lifestyle, and ways to increase the effectiveness of classes.